Measuring productivity dispersion in selected Australian industries - Simon Campbell; Thai Nguyen; Alexander Sibelle; Franklin Soriano (The Australian Government, The Treasury, 2019)
Productivity growth is a key determinant of improvements in living standards in the long run. However, analysis of productivity trends at the aggregate level does not capture the variation of firm and sub-industry productivity performance that underlies industry or aggregate productivity. By examining the differences in productivity performance of firms in particular industries (i.e. productivity dispersion) we can enhance our understanding of the rich productivity dynamics of the economy and ultimately help to better inform policy advice. This paper - a collaboration between Treasury and the Australian Bureau of Statistics - uses firm-level data from the Business Longitudinal Analysis Data Environment (BLADE) to measure the dispersion in labour productivity for six Australian industries (Manufacturing; Construction; Retail Trade; Wholesale Trade; Professional, Scientific and Technical Services; and Administrative and Support Services). The study finds labour productivity dispersion to be persistent in the selected industries. Among the six industries, Manufacturing and Professional, Scientific and Technical Services exhibit the smallest labour productivity gap between businesses at the top and bottom quartiles. Contrary to international evidence, there is little evidence of widening labour productivity dispersion over time, with dispersion decreasing to varying degrees over 2001-02 to 2013‑14. In particular, labour productivity dispersion declined significantly over the period in Retail Trade and Wholesale Trade. We also explore potential drivers of labour productivity dispersion and its relationship with aggregate labour productivity, and discuss avenues for further research.
Keywords: C23; C55; D22; D30; E23; E24; 330; productivity; dispersion; firm-level; BLADE